An Experimental and Numerical Study on Charged 21700 Lithium-Ion Battery Cells under Dynamic and High Mechanical Loads - Bulla, Marian; Schmandt, Christopher; Kolling, Stefan; Kisters, Thomas; Sahraei, Elham (Energies (Basel), 2023)
The need for higher capacity battery cells has increased significantly during the past years. Therefore, the subject of this study is to investigate the behavior of high performance 21700 Lithium-Ion cylindric battery cells under several abuse conditions, represented by high mechanical loads with different velocities and states of charge (SoC), and to develop a finite element analysis (FEA) model, using the OpenRadioss’ explicit solver capabilities. The present study is focused on the investigation of the behavior of these cells under high mechanical loads with different loading velocities and different states of charge. The aim of the study is to provide a tool to predict the point of an internal short circuit in FEA, with a very good approximation. Experiments were completed using a hydraulic flat-compression test, set up at four different states of charge, 40%, 60%, 80% and 100%, and three different loading velocities of 10 mms−1, 100 mms−1 and 1000 mms−1. A homogenized FEA model is developed to predict the internal damage of the separator, which can lead to a short circuit with a possible thermal runaway under abusive load conditions. The present model, in combination with well identified material and fracture parameters, succeeded in the prediction of the mechanical behavior at various states of charge and mechanical loading conditions; it can also be used for further crashworthiness analysis within a full-car FEA model. This accurate cell model will be the first building block to optimize the protective structures of batteries in electric vehicles, and reduce their weight through a deeper understanding of their overall behavior during the different crash cases.